Republic of Mozambique : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Republic of Mozambique's Request for Disbursement Under the Rapid Credit Facility (RCF). Mozambique is expected to be significantly affected by the coronavirus disease 2019 pandemic, dashing prospects of a nascent economic recovery following two powerful tropical cyclones that struck in 2019. The IMF's emergency financial support under the RCF, along with the additional donor grant financing it will help to catalyze, will contribute to addressing Mozambique's urgent balance of payments needs generated by the pandemic. The authorities are committed to prevent corruption and misuse of emergency financing, by strengthening transparency and accountability. In this connection, they will publish large public procurement contracts and conduct and publish ex-post audits of funds' use. Once the pandemic eases, it will be critical to resume fiscal consolidation and strengthened debt management and transparency to ensure that public debt remains sustainable. It will also be important to implement structural reforms to support inclusive and sustainable growth.